Sex differences underlying preexisting cardiovascular disease and cardiovascular injury in COVID-19. (November 2020) - Medzikovic, Lejla; Cunningham, Christine M.; Li, Min; Amjedi, Marjan; Hong, Jason; Ruffenach, Gregoire; Eghbali, Mansoureh
Abstract: The novel 2019 coronavirus disease (COVID-19), resulting from severe acute respiratory syndrome coronarvirus-2 (SARS-CoV-2) infection, typically leads to respiratory failure in severe cases; however, cardiovascular injury is reported to contribute to a substantial proportion of COVID-19 deaths. Preexisting cardiovascular disease (CVD) is among the most common risk factors for hospitalization and death in COVID-19 patients, and the pathogenic mechanisms of COVID-19 disease progression itself may promote the development of cardiovascular injury, increasing risk of in-hospital death. Sex differences in COVID-19 are becoming more apparent as mounting data indicate that males seem to be disproportionately at risk of severe COVID-19 outcome due to preexisting CVD and COVID-19-related cardiovascular injury. In this review, we will provide a basic science perspective on current clinical observations in this rapidly evolving field and discuss the interplay sex differences, preexisting CVD and COVID-19-related cardiac injury. Graphical abstract: Unlabelled Image Highlights: Cardiovascular complications are prominent in COVID-19. Preexisting cardiovascular disease is a risk factor for COVID-19 severity. Cardiovascular disease, smoking and obesity burden more male COVID-19 patients Cardiac injury and systemic inflammation are pronounced in male COVID-19 patients. No sex disparities were observed in arrhythmia and thrombosis in COVID-19 patients.